Talk Is Silver, Code Is Gold? Beyond Traditional Notions of Contribution in Peer Production: The Case of Drupal - Rozas, David; Gilbert, Nigel; Hodkinson, Paul; Hassan, Samer (Frontiers in Human Dynamics, 2021)
Peer production communities are based on the collaboration of communities of people, mediated by the Internet, typically to create digital commons, as in Wikipedia or free software. The contribution activities around the creation of such commons (e.g. source code, articles or documentation) have been widely explored. However, other types of contribution whose focus is directed towards the community have remained significantly less visible (e.g. the organisation of events or mentoring). This work challenges the notion of contribution in peer production through an in-depth qualitative study of a prominent “code-centric" example: the case of the free software project Drupal. Involving the collaboration of more than a million participants, the Drupal project supports nearly 2% of websites worldwide. This research (1) offers empirical evidence of the perception of “community-oriented" activities as contributions, and (2) analyses their lack of visibility in the digital platforms of collaboration. Therefore, through the exploration of a complex and “code-centric” case, this study aims to broaden our understanding of the notion of contribution in peer production communities, incorporating new kinds of contributions customarily left invisible.